The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fphys.2019.00819
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Verification of MicroRNA-16 Family Targeting Intestinal Divalent Metal Transporter 1 (DMT1) in vitro and in vivo

Abstract: Divalent metal transporter 1 (DMT1) is a key transporter of iron uptake and delivering in human and animals. However, post-transcriptional regulation of DMT1 is poorly understood. In this study, bioinformatic algorithms (TargetScan, PITA, miRanda, and miRDB) were applied to predict, screen, analyze, and obtain microRNA-16 family members (miR-16, miR-195, miR-497, and miR-15b) targeting DMT1, seed sequence and their binding sites within DMT1 3′ untranslated region (3′ UTR) region. As demonstrated by dual-lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…miR-Let-7d binds to the 3′-UTR of DMT1-IRE decreasing its expression at both the mRNA and protein levels in K562 and HEL cells ( 81 ). miR-16 family members miR-16, miR-195, miR-497 and miR-15b have been shown to suppress intestinal DMT1 expression by targeting DMT1 3′-UTR in HCT116 cells ( 82 ). These miRNAs may be involved in ferroptosis by targeting DMT1.…”
Section: Role Of Ncrnas In Ferroptosis and Cancer Developmentmentioning
confidence: 99%
“…miR-Let-7d binds to the 3′-UTR of DMT1-IRE decreasing its expression at both the mRNA and protein levels in K562 and HEL cells ( 81 ). miR-16 family members miR-16, miR-195, miR-497 and miR-15b have been shown to suppress intestinal DMT1 expression by targeting DMT1 3′-UTR in HCT116 cells ( 82 ). These miRNAs may be involved in ferroptosis by targeting DMT1.…”
Section: Role Of Ncrnas In Ferroptosis and Cancer Developmentmentioning
confidence: 99%
“…However, the regulatory miRNA of agrin has not been reported. In this study, we searched for putative miRNAs by using common prediction algorithms (miRDB, miRanda, and TargetScan) and selected three miRNAs with high scores in at least 2 algorithms simultaneously, as reported previously (Gong et al, 2015;Jiang et al, 2019). Subsequent studies indicated that only miR-144 could regulate the expression of agrin, and miR-144/agrin/MuSK axis might regulate NMJ formation in nerve sprouting and the development of original motor endplates.…”
Section: Discussionmentioning
confidence: 96%
“…After 1 week of acclimatization, mice were divided into a negative control group (miR-SC, n = 15) and a miR-20b over-expression group (miR-20b, n = 15) and were subjected to the same diets. Plasmid transfection was performed with some modifications based on previous studies [30]. Briefly, 20 μg pcDNA3.1(+)-miRNAs plasmid (miR-SC or miR-20b) in 150 μL Opti-MEM medium (31985-070, Gibco, Carlsbad, California, USA) was mixed with 25 μL lipofectamine 2000 in 150 μL Opti-MEM medium, and the total mixture (300 μL) was incubated for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…MiR-let-7d induces iron accumulation in endosomes by suppressing expression of an isoform of divalent metal transporter 1 (DMT1) of K562 cells [29]. In vitro and in vivo studies showed that the miRNA-16 family (miR-15b, miR-16, miR-195 and miR-497) inhibits the expression of intestinal DMT1 [30]. MiR-485-3p and miR-20a regulate intracellular iron homeostasis by directly targeting FPN, an iron exporting gene in lung cancer and HepG2 cells, respectively [31,32].…”
Section: Introductionmentioning
confidence: 99%